Does competition standard and player position influence the match-play physical demands of Australian elite youth male soccer players within a single squad?. Issue 2 (April 2021) - Sydney, Michael G; Ball, Nick; Chapman, Dale; Wollin, Martin; Mara, Jocelyn K
The purpose of this study was to investigate the influence of competition standard and player position on the physical demands of Australian elite youth male soccer players during match-play. Twenty-three elite youth male soccer players from the same Australian U17 National Centre of Excellence program were observed across 8 National Youth League (NYL) and 21 National Premier League (NPL) competition matches. Total (TD/min), low- (< 3.6 m/s), moderate- (3.6–5.0m/s) and high-speed (> 5.0 m/s) running distance, and the accelerations (Acc/min) (≥ 2.0 m/s 2 ) and decelerations (Dec/min) (≤ −2.0 m/s 2 ) were recorded using 15-Hz portable global positioning system tracking devices (GPSports, Canberra, Australia). An interaction was observed between competition standard and player position for TD/min ( p = 0.003), HSRD/min ( p = 0.007) and Acc/min ( p = 0.037) indicating the influence that competition standard had on these variables varied according to player position. Furthermore, we report that Central Defenders (3.1%), External Attackers (4.2%) and Central Attackers (3.8%) performed more TD/min in NYL (professional development level) compared to NPL (semi-professional) match-play. Central Defenders (24.2%) and Central Attackers (17.0%) completed more HSRD/min in NYL (professional development level) compared to NPL (semi-professional) match-play. Central Defenders (47.8%), External Defenders (20.5%), Midfielders (18.5%) and External Attackers (32.3%) all performed more Acc/min in NPL (semi-professional) when compared to NYL (professional development level) match-play. The results of this study provide scientific basis to aid the match-preparation of Australian elite youth male soccer player's transition to higher standards of soccer.